Severe acute ocular hypertension following pulsed methylprednisolone for juvenile idiopathic arthritis - Beverstock, Andrew (BMJ Case Rep, 2019)
We report the case of a 6-year-old girl with juvenile idiopathic arthritis and anterior uveitis who was treated with two doses of intravenous methylprednisolone for acute arthritis. She developed severe ocular hypertension (intraocular pressures (IOPs) of 54 mm Hg in the right eye and 61 mm Hg in the left eye) requiring inpatient therapy with intravenous acetazolamide. The normal range of values for IOP is 12–22 mm Hg. This severe case of acute intraocular hypertension due to systemic steroids highlights the need to consider monitoring of IOPs for children on high-dose topical and systemic steroids with risk factors for raised IOP.